Literature Reviews: Hydrometeorological Disasters and Climate Change Adaptation Efforts - Putra, Aprizon; Dewata, Indang; Gusman, Mulya (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
Climate change has had an impact on increasing hydrometeorological disasters in Indonesia. the Meteorology, Climatology and Geophysics Agency (BMKG) estimates, until mid-May 2020 Indonesia is threatened with a hydrometeorological disaster. Most of the Indonesian people are in areas prone to hydrometeorological disasters. To reduce its impact, the government needs to make adaptation efforts to climate change, which are carried out holistically and integrated by involving all elements of society and the government by referring to the National Action Plan for Climate Change Adaptation in Indonesia that has been prepared by the government of Indonesia.